Pulmonary function and and muscle strength assessment in individuals who perform the Low Pressure Fitness (LPF) technique: cross-sectional study (Research, Society and Development, 2022)
The present research aimed to assess whether the use of the Low Pressure Fitness technique, which consists of performing a negative abdominal pressure and, for this purpose, uses the contraction of the diaphragm muscle, which is the main responsible for a large part of inspiration and expiration, alters lung function and muscular strength of respiratory muscles in volunteers practicing this technique. The methods used for evaluation and measurement were: simple spirometry and manovacuometry with assessment of maximal inspiratory pressure and maximal expiratory pressure. Six individuals were evaluated, 5 women and 1 man, who had been performing the technique for at least one year, and who had not been diagnosed with pulmonary disease. Regarding the spirometric indices, the following averages of the % of predicted values were observed: FVC(L) = 90.00%; FEV1(L) = 101.66%; FEV1/CFV = 95.83%; FEF25-75%(L/s) = 90.83%; PFR(L/S) = 95.33%. As for muscle strength parameters, an average of % of the predicted value of maximum Inspiratory pressure of 81.05% and of maximum expiratory pressure of 86.64% was observed. Thus, spirometric values within the normal range were observed and, contrary to what would be expected, the variables of maximal inspiratory and expiratory pressure did not indicate a gain in respiratory muscle strength. In this way, the results obtained demonstrate that there was no change in pulmonary function when compared with the predicted values, while in measuring respiratory muscle strength, we obtained values below the reference for maximal inspiratory pressure and maximal expiratory pressure. It is concluded that, even if the volunteers mastered the contraction of these muscles, there was no change in lung function and no gain in respiratory muscle strength.